Students’ Perception Towards Education Cost: Case Study on Education Faculty Students of IKIP PGRI Semarang in 2012 - Tatik Sutarti Suryo; Maryadi Maryadi (Jurnal Penelitian Pendidikan, 2013)
Education cost is very important for the continuity of an education board and the smoothness for the students themselves. The education cost should be more human impartial in determining the above education cost by paying attention to the quality, social economical of the society, so that accessibility is till maintained. This deals with the education cost which becomes the central issue in education field. This education cost covers direct cost and indirect cost with the consideration in determining the education cost to be more understandable and empirical rational, so that to be created education life which is much more human and still depends on educational reality which is always concerning with the quality demand and society accessibility.